Content of Erucic Acid in Edible Oils and Mustard by Quantitative 13 C NMR - Kok, Wai Ming; Mainal, Azizah; Chuah, Cheng Hock; Cheng, Sit Foon (Wiley, 2017)
High content of erucic acid in foods and edible oils is a major concern. The excessive consumption of erucic acid has been linked to heart diseases. Therefore, accurate, rapid, and direct analysis of the erucic acid content is particularly crucial. However, most of the analytical methods involve time-consuming sample preparation and chromatography analyses. As a result, quantitative 13C NMR is developed and the total content of erucic acid in a wide variety of edible oils and mustard products are analyzed within 58 min. Meanwhile, the positional distribution of fatty acids in triacylglycerols and mustard products can be done effortlessly. An additional peak, namely, erucic acid peak is detected at 173.19 ppm has not been reported previously. Apart from that, the detection limit of erucic acid (0.98% [m m−1]) and coefficient of determination (R2 = 0.9977) both are investigated by the current method. The total content of erucic acid shows an excellent quantitative relation between reference method (gas chromatography) and quantitative 13C NMR. In this study, mustard oil and few mustard products exceed the permitted maximum levels established for erucic acid (European Union: 5%, United State: 2%). Practical Applications: Erucic acid in mustard products and edible oils are determined. The excessive consumption of erucic acid can cause some healthy problems. Therefore, more attention should be paid to the tolerable intake of erucic acid. The results of this study can be applied to monitor and quantify the erucic acid content quickly in a wide variety of edible oils and mustard products without any laborious chemical derivatization prior to the analysis. Quick determination and quantification of erucic acid in dietary oils including mustard and its products, is achieved using quantitative 13C NMR. Besides that, regiospecific data of the oisl and products are also available from the same analysis.